Cures and currency in Donne’s letters to patrons - Bumke, Alison (Johns Hopkins University Press, 2017)
Critics have discussed how John Donne’s writing responds to alchemy and to patronage, but none has examined how he draws parallels between the two frameworks. Donne sees both as convoluted, frustrating processes that rely on falseness. Comparing his praise to alchemical coins—the quality of which was considered dubious—he attempts to persuade patrons that his flattering epistles are nonetheless “currant” in possessing both social relevance and monetary value. Reading these letters alongside contemporary alchemical tracts, this article traces how Donne’s references to alchemy explore the complex relationships between verse and value in the Jacobean Court.